2021
DOI: 10.3389/fpsyt.2021.770154
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Online Resource for People Bereaved by Suicide: A Mixed-Method User-Centered Study Protocol

Abstract: Introduction: Suicide bereavement is known to be highly distressing and is frequently associated with mental health problems. Despite high-level of need regarding mental and physical health, people bereaved by suicide display low level of help-seeking and perceived support in the aftermath of the loss. The lack of accessibility and reliability of face-to-face counseling resources is notably reported by suicide survivors. Online resources can enhance early access to help and support for people bereaved by suici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…There is some evidence to support this hypothesis, and several studies have reported an increased suicide risk and impaired mental health on bereavement anniversaries [30][31][32][33][34], while a recent study did not nd any evidence of an elevated suicide risk around anniversaries in people bereaved by suicide [35]. Digital resources, such as memorial-based websites, may offer new ways to contact and support bereaved people [12,17] and to implement innovative and adaptive prevention strategies to reduce the deleterious effects of bereavement anniversaries on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence to support this hypothesis, and several studies have reported an increased suicide risk and impaired mental health on bereavement anniversaries [30][31][32][33][34], while a recent study did not nd any evidence of an elevated suicide risk around anniversaries in people bereaved by suicide [35]. Digital resources, such as memorial-based websites, may offer new ways to contact and support bereaved people [12,17] and to implement innovative and adaptive prevention strategies to reduce the deleterious effects of bereavement anniversaries on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The ISR framework employs various design processes to build a product or design an artifact, such as a mental health online resource [ 22 , 23 ]. The protocol of the study has been exhaustively described elsewhere [ 24 , 25 ]. In this article, we describe the results of the first quantitative stage of the study, namely, the relevance cycle , which aimed to collect the use, needs and expectations of people bereaved by suicide regarding the internet and social media.…”
Section: Methodsmentioning
confidence: 99%
“…Through exploring the relational dynamics of a community bound by a common traumatic experience, this paper expands on studies studying the communication practices of how suicide bereavement needs are expressed in online communities (Bailey, Bell, and Kennedy 2015;Bailey et al 2017;Bell, Bailey, and Kennedy 2015;Krysinska and Andriessen 2017;Leaune et al 2021;Perusse 2021).…”
Section: The Suicide Epidemic and Social Mediamentioning
confidence: 99%
“…The loss of a loved one to suicide is one of the most challenging events a person can endure. It is a loss that is often unexpected, leading to feelings of hopelessness, powerlessness, guilt, and isolation (Cerel et al 2014(Cerel et al , 2019Leaune et al 2021;Mitchell et al 2003;Neimeyer 2012;Neimeyer and Pfeiffer 1994;Shields, Kavanagh, and Russo 2017). The stigma of suicide is deeply internalized throughout social discourse (Hanschmidt et al 2016;Pitman et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation